Vivre la mort: À propos de B. Humbert, Vivre la mort : Nous pouvons réapprendre à mourir (2023) - Tranchant, Emmanuel (Nouvelle revue théologique, 2024)
At the start of the 3rd millennium, the anthropological breakdown of our humanity - the very appearance of the term in everyday language is a sign of its weakening in our community - stems from the disturbance in our representations of life and death.